(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the issue of developing students' professional competencies based on imitative models. The theoretical and practical aspects of imitative teaching, their role in improving the quality of education are considered. Methods of forming professional competencies using virtual simulations, role-playing games and technological platforms are analyzed. The results of the study are aimed at determining how imitative models affect the educational process and providing recommendations for their effective implementation.